Vermicompost Supplementation Improves the Stability of Bioactive Anthocyanin and Phenolic Compounds in Clinacanthus nutans Lindau - Zuhaili Yusof; Sujatha Ramasamy; Noor Zalina Mahmood; Jamilah Syafawati Yaacob (Molecules, 2018)
This project studied the effect of vermicompost application on the composition of bioactive anthocyanin and phenolic compounds, and the antioxidant activity of Clinacanthus nutans. The correlation between the bioactive constituents and antioxidant capacity was also evaluated. In this project, a field study was conducted using a randomized complete block design (RCBD) with four treatment groups, including control plants (CC), plants supplied with chemical fertilizer (CF), plants supplied with vermicompost (VC), and plants supplied with mixed fertilizer (MF). The leaves of C. nutans from all treatment groups were harvested, subjected to solvent extraction, and used for quantification of total anthocyanin content (TAC), total phenolic content (TPC), and total flavonoid content (TFC). The initial antioxidant activity of the extracts was evaluated using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays, as well as after two and four weeks of storage at −20 °C and 4 °C. Data analysis showed that CC plants contained the highest TAC (2180.14 ± 338.43 µg/g dry weight) and TFC (276.25 ± 3.09 mg QE/g dry weight). On the other hand, CF plants showed the highest TPC (181.53 ± 35.58 mg GAE/g dry weight). Moreover, we found that CC plants had the highest antioxidant potential against DPPH radicals whereas MF plants showed the lowest antioxidant potential. After four weeks of extract storage at −20 °C and 4 °C, the TPC, TFC, TAC, and antioxidant potential of the extracts decreased. Extracts from VC showed the lowest percentage of total phenolic and total flavonoid loss after extract storage at −20 °C and 4 °C compared with other plant extracts. At this juncture, it could be deduced that the application of vermicompost had little effect on the expression of phenolics, flavonoids, or anthocyanin in C. nutans. However, the extract from plants treated with vermicompost (VC and MF) showed better stability compared with CC and CF after extract storage at different temperatures.